Hubungan Antara Toleransi Sosial, Keakraban dengan Sumpek pada Penghuni Pemukiman Padat di Kota Surakarta - Indra Wahyudi (Jurnal Psikologi, 2018)
The purpose of this study is to find the relationship between social tolerance and intimacy with the crowded feeling in densely populated residents in Surakarta.According to BPS’ research in 2014, Surakarta is the most densely populated city in the province of Central Java. Hence, it can be predicted that the residents who live in the pockets of highly-densed areas of the densest districts, feel overwhelmingly crowded.  However, the crowded feeling does not have to be occured by the residents who live in highly-densed areas if they oftenly socialize with each other. The crowded feeling also does not need to occur in highly-densed areas if the residents have mutual tolerance, mutual respect, or social tolerance toward each other.Frequent social interaction will build a sense of intimacy. Hence, the residents can see the positive sides of each other. It is expected that this intimacy is reducing crowded feeling of the residents in highly-densed areas.The role of social tolerance is really important for the implementation of the embodiment from the idea of living together with others in harmony as developed in Java, as Surakarta has been known as one of Javanese cultural center other than Yogyakarta.Social tolerance enables densely populated residents to refrain from the inconvenience of others. Hence, they are adaptable with each other’s behavior.Purusant to the aforementioned background, following are three hypotheses which can be constructed:  Major: There is a negative relationship between intimacy, social tolerance and crowded feeling [there are densely populated residents in the city of Surakarta.]Minor1: There is a negative relationship between social tolerance and crowded feeling.Minor2: There is a negative relationship between intimacy and crowded feeling. The sampling technique used in this study is area random sampling, using two of the most densed population of RT 03 and RT 04 from RW 10 in Danukusuman sub-district as the representatation of Serengan Subdistrict, which is the densest area in Surakarta with 93 research samples.The research results that simultaneously, social tolerance and intimacy are able to decrease the crowd feeling significantly, with the result of R = -0.396, p = 0,00.Partially, social tolerance is also able to decrease the crowded feeling significantly with the result of rx1y-x2 = -0,363 p = 0.00. However, intimacy cannot be able to decrease the crowded feeling with rx2y-x1 = -0.137 p = 0.197. Keywords: Social Tolerance.  The purpose of this study is to find therelationship between social tolerance and intimacywith the crowded feeling in densely populated residents inSurakarta. According to BPS’research in 2014, Surakarta is the most densely populated city in the province of CentralJava. Hence, it can be predicted that the residents who live in the pockets of highly-densedareas of the densest districts, feel overwhelmingly crowded. However, the crowded feelingdoes not have to be occured by the residents who live in highly-densed areas if they oftenlysocialize with each other. The crowded feeling also does not need to occur in highly-densedareas if the residents have mutual tolerance, mutual respect, or social tolerance toward eachother.Frequent social interaction will build a sense of intimacy. Hence, the residents can seethe positive sides of each other. It is expected that this intimacy is reducing crowded feelingof the residents in highly-densed areas.The role of social tolerance is really important for theimplementation of the embodiment from theidea of living together with others in harmony asdeveloped in Java, as Surakarta has been known as one of Javanese cultural center otherthan Yogyakarta. Social tolerance enables densely populated residents to refrain from theinconvenience of others. Hence, they are adaptable with each other’s behavior. Purusant tothe aforementioned background, following are three hypotheses which can be constructed:Major: There is a negative relationship between intimacy, social tolerance andcrowded feeling [there are densely populated residents in the city of Surakarta.]Minor1: There is a negative relationship between social tolerance and crowdedfeeling.Minor2: There is a negative relationship between intimacy and crowded feeling.The sampling technique used inthis study is area random sampling, using two of the mostdensed population of RT 03 and RT 04 from RW 10 in Danukusuman sub-district as therepresentatation of Serengan Subdistrict, which is the densest area in Surakarta with 93research samples.The research results that simultaneously, social tolerance and intimacy are able to decreasethe crowd feeling significantly, with the result of R =-0.396, p = 0,00.Partially, social tolerance is also able to decrease the crowded feeling significantly with theresult of rx1y-x2 =-0,363 p = 0.00. However, intimacy cannot be able to decrease thecrowded feeling with rx2y-x1 =-0.137 p = 0.197.Keywords: Social Tolerance.